Template for robust soft-body crawling with reflex-triggered gripping. (4th February 2015) - Schuldt, Dieter W; Rife, Jason; Trimmer, Barry
Abstract: Caterpillars show a remarkable ability to get around in complex environments (e.g. tree branches). Part of this is attributable to crochets which allow the animal to firmly attach to a wide range of substrates. This introduces an additional challenge to locomotion, however, as the caterpillar needs a way to coordinate the release of the crochets and the activation of muscles to adjust body posture. Typical control models have focused on global coordination through a central pattern generator (CPG). This paper develops an alternative to the CPG, which accomplishes the same task and is robust to a wide range of body properties and control parameter variation. A one-dimensional model is proposed which consists of lumped masses connected by a network of springs, dampers and muscles. Computer simulations of the controller/model system are performed to verify its robustness and to permit comparison between the generated gaits and those observed in real caterpillars (specifically Manduca sexta .).